Nutritional considerations for vegetarian athletes: A narrative review - Luna, Fernando (2024)
In recent times, we have witnessed a growing interest in vegetarian diets among the sports community. Athletes follow these dietary patterns for various reasons, including health benefits, sustainability, animal welfare and spirituality. However, because some studies have shown a negative effect of vegetarian diets on physical performance, there is a prevailing concern that a vegetarian diet may not fully meet athletes´nutritional requirements. Therefore, in this narrative review, we comprehensively examine the nutritional considerations relevant to athletes adhering to various types of vegetarian diets. In particular, we analyze the evidence regarding energy, macronutrients, micronutrients and creatine. The current evidence suggests that well-planned vegetarian diets, which may include eggs and dairy, are suitable for meeting the specific requirements of athletes and allow performance levels similar to those observed in athletes with other well-planned dietary patterns. In addition, there is evidence highlighting the potential of vegetarian diets in reducing the risk of non-communicable diseases such as cardiovascular disease, type 2 diabetes and some cancers. However, vegetarian athletes need to be mindful of their dietary planning to avoid deficiencies in certain critical nutrients present in lower concentrations in vegetarian diets or whose absorption is hindered by certain chemical compounds found in plants. Thus, further research is needed in order to clarify some aspects of vegetarian nutrition in athletes.